Changes in mortality rates during the larval stage of the Pacic white shrimp (Litopenaeus vannamei) on the basis of algal (Chaetoceros calcitrans or Tetraselmis suecica) food density - Pérez-Morales, Alfredo; Band-Schmidt, Christine J.; Martínez-Díaz, Sergio F. (Ecosistemas y Recursos Agropecuarios, 2016)
In the shrimp culture, larval stages have high mortality rates, particularly in the zoea stage, this because to the star of phytoplankton feeding and an inadequate microalga species and cell density used in commercial hatcheries. Several microalgae species are used as food in shrimp larviculture, and the most common are Chaetoceros calcitrans and Tetraselmis suecica. Therefore, in this study, we quantied changes in the mortality rates of zoea larvae of L. vannamei fed either C. calcitrans or T. suecica at dierent cell densities. Results showed higher mortality rates when fed L. vannamei larvae with T. suecica than C. calcitrans. This study demonstrates that when zoea begin to feed on phytoplankton, they are highly sensitive to the microalga diet and cell densities supplied, which signicantly aect the survival of L. vannamei larvae.